Computerized Engine Controls, 11th Edition - Steve Hatch (Cengage Learning, 2020)
Providing thorough coverage of both fundamental electrical concepts and current automotive electronic systems, COMPUTERIZED ENGINE CONTROLS, Eleventh Edition, equips readers with the essential knowledge they need to successfully diagnose and repair modern automotive systems. Reflecting the latest technological advances from the field, the Eleventh Edition offers updated and expanded coverage of diagnostic concepts, equipment, and approaches used by today's professionals. All photos and illustrations are now printed in full, vibrant color, making it easier for today's visual learners to engage with the material and connect chapter concepts to real-world applications. Drawing on abundant, firsthand industry experience, the author provides in-depth insights into cutting-edge topics such as hybrid and fuel cell vehicles, automotive multiplexing systems, and advanced driver assist systems. In addition, key concepts are reinforced with ASE-style end-of-chapter questions to help prepare readers for certification and career success. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.